GAYA PENYUTRADARAAN IMPRESIONISME PADA FILM SANG KIAI - Widiyatmaka, Wegig; Candra DA., NRA. (Capture : Jurnal Seni Media Rekam, 2015)
The research studied about movie entitled Sang Kiai created by Rako Prijanto. The movie achieved predicate of the best film and the best director in the Indonesia Film Festival 2013 in Semarang. Research problems in the study focused on style of directing â€œimpressionismâ€ in Sang Kiai movie with two aspects namely narrative and cinematic. Both aspects can used for reference in understanding of narrating a fiction movie. The objective of the research was to find out style of impressionism directing in the Sang Kiai movie as a technique of narrating film. The study applied the descriptive qualitative method with the researcher as a key instrument to collect data and review of related literature to support the style of impressionism in the film â€˜Sang Kiaiâ€™. The data analysis process was conducted through some steps: data collection, data reduction, data analysis, and conclusion. The findings of the research showed that the Sang Kiai movie was a kind of impressionism film in narrating the story. In the display, it was emphasized more on the cinematography and editing to give perception on the characters in the movie, in order that it achieved the narration of the story through narrative and cinematic aspects.Kata Kunci: Style, impresionism, Sang Kiai, and movie